2017
DOI: 10.1002/ceas.12056
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Researcher Identity Development of Counselor Education and Supervision Doctoral Students

Abstract: Counselor education and supervision (CES) doctoral students play an important role in contributing to knowledge in the counseling profession. CES doctoral students were interviewed to explore their researcher identity, a unique self‐concept that possibly includes research self‐efficacy and interest. Issues critical to facilitating researcher identity development included confidence, the researcher voice, faculty support, and opportunities for research.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
25
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 19 publications
3
25
0
Order By: Relevance
“…Specifically, they hypothesized, and empirically supported, that the research training environment during doctoral studies is positively related to research self‐efficacy and research interest, which both in turn influence scholarly activity of psychology doctoral students (Kahn, 2001). Since then, researchers have found that the combination of these factors lead to increased scholarly productivity among doctoral students in psychology (Deemer, Martens, Haase, & Jome, 2009; Hemmings & Kay, 2016; Kahn & Schlosser, 2010; Pasupathy & Siwatu, 2014), as well as in counselor education (Kuo, Woo, & Bang, 2017; Lamar & Helm, 2017; Lambie & Vaccaro, 2011). What is unknown is whether this model would apply to new counselor educators’ scholarship.…”
mentioning
confidence: 99%
“…Specifically, they hypothesized, and empirically supported, that the research training environment during doctoral studies is positively related to research self‐efficacy and research interest, which both in turn influence scholarly activity of psychology doctoral students (Kahn, 2001). Since then, researchers have found that the combination of these factors lead to increased scholarly productivity among doctoral students in psychology (Deemer, Martens, Haase, & Jome, 2009; Hemmings & Kay, 2016; Kahn & Schlosser, 2010; Pasupathy & Siwatu, 2014), as well as in counselor education (Kuo, Woo, & Bang, 2017; Lamar & Helm, 2017; Lambie & Vaccaro, 2011). What is unknown is whether this model would apply to new counselor educators’ scholarship.…”
mentioning
confidence: 99%
“…Research regarding doctoral student stakeholders ( n = 4) included attention to impact of post‐master’s experience during doctoral study on each of five core professional identity areas, with evidence of greatest impact in leadership and advocacy and supervision areas (Farmer et al, 2017). Lamar and Helm (2017) contributed a grounded theory of doctoral student researcher identity development, and Kuo, Woo, and Bang (2017) demonstrated support for complex relationships between research self‐efficacy, motivation, advisory relationship, and productivity. Relatedly, Boswell, Stark, Wilson, and Onwuegbuzie (2017) found that doctoral advisees who experienced dual roles with their mentors had more positive career‐related functions compared with those with single‐role relationships.…”
Section: Understanding Stakeholdersmentioning
confidence: 99%
“…Considering the important role of scholarly publication in counselor education and emerging scholars' training needs, a more holistic understanding of doctoral students' research and publication experiences is needed in the counselor education literature. Understanding how student writers develop, and how their academic growth can be facilitated, is imperative, as it helps counselor educators effectively prepare doctoral students sustain a successful research career (Lamar & Helm, 2017). Therefore, the current study will examine what doctoral student researchers experienced while developing their manuscripts, submitting them for publication, and accommodating editorial feedback.…”
Section: Doctoral Students' Publicationmentioning
confidence: 99%
“…As evidence-based practice has become an important focus of the counseling profession, researcher identity has emerged as one critical component of counseling students' professional development (Jorgensen & Duncan, 2015b;Reisetter et al, 2004). Lamar and Helm (2017) argued that a strong researcher identity facilitates students' commitment to research, which ultimately advances the profession by emphasizing the rigor of research. They also noted that research skill development did not automatically translate to the development of researcher identity, although previous research (e.g., and CACREP 2016 Standards mostly highlight only the research skills needed by doctoral students.…”
Section: Researcher Identity Developmentmentioning
confidence: 99%
See 1 more Smart Citation